2022
DOI: 10.1002/fsn3.3080
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol extracts of Chinese bayberry branch induce S‐phase arrest and apoptosis in HepG2 cells

Abstract: The alcohol extracts of Chinese bayberry (Myrica rubra) branches (MRBE) are rich in flavonoids which have a variety of medicinal benefits, but their effects on human HepG2 were unknown. In this study, the effects of MRBE on HepG2 cell growth and its potential for inhibiting cancer were explored. The results displayed that MRBE inhibited HepG2 proliferation both by arresting cells in S phase and promoting apoptosis. Quantitative reverse‐transcription PCR (qRT‐PCR), western blotting, and immunofluorescence showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Bayberry produced by the Myrica rubra tree is a subtropical fruit with a unique sweet and sour taste native to southern China, which is commercially cultivated in many areas of China, including Zhejiang, Guizhou, Guangxi and Yunnan provinces, and has become an important economic pillar for local mountain farmers [ 1 , 2 , 3 ]. Besides its economic significance, recent studies have shown that bayberry also has nutritional and medicinal value; indeed, its extracts exhibit anti-cancer and anti-oxidant activity, making this a promising fruit regarding its potential to be industrially processed for high-value-added food products [ 4 , 5 , 6 , 7 , 8 ]. However, in recent years, bayberry production has been threatened by a devastating disease called twig blight, which is caused by the ascomycete fungi Pestalotiopsis versicolor and P. microspore [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bayberry produced by the Myrica rubra tree is a subtropical fruit with a unique sweet and sour taste native to southern China, which is commercially cultivated in many areas of China, including Zhejiang, Guizhou, Guangxi and Yunnan provinces, and has become an important economic pillar for local mountain farmers [ 1 , 2 , 3 ]. Besides its economic significance, recent studies have shown that bayberry also has nutritional and medicinal value; indeed, its extracts exhibit anti-cancer and anti-oxidant activity, making this a promising fruit regarding its potential to be industrially processed for high-value-added food products [ 4 , 5 , 6 , 7 , 8 ]. However, in recent years, bayberry production has been threatened by a devastating disease called twig blight, which is caused by the ascomycete fungi Pestalotiopsis versicolor and P. microspore [ 9 ].…”
Section: Introductionmentioning
confidence: 99%